2019
DOI: 10.1007/s00394-019-02072-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal probiotic milk intake during pregnancy and breastfeeding complications in the Norwegian Mother and Child Cohort Study

Abstract: Purpose During the time of breastfeeding, a third of all women contract (or: fall ill in) mastitis—the leading cause of precocious weaning. Recent studies indicate that probiotics intake may prevent mastitis by altering the breast’s bacterial flora. The aim of this study was to examine whether probiotic milk intake during pregnancy is associated with less breastfeeding complications and longer breastfeeding duration. Methods This study included 57,134 women, with live singleton term births, participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Our finding that early‐onset mastitis is associated with premature cessation of breastfeeding is supported by a number of previous studies 9,10,32 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that early‐onset mastitis is associated with premature cessation of breastfeeding is supported by a number of previous studies 9,10,32 …”
Section: Discussionsupporting
confidence: 89%
“…Our finding that early-onset mastitis is associated with premature cessation of breastfeeding is supported by a number of previous studies. 9,10,32 That said, the absolute effects of mastitis on breastfeeding outcome appear small. Our observed associations between early mastitis and poorer breastfeeding outcomes correspond to absolute reductions of 2.5% and 1.2% in terms of the number of women reporting any or predominant breastfeeding for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the probiotic group had a 58% lower prevalence of experiencing mastitis [ 113 ]. In addition, Karlsson et al performed a cohort survey of more than 50,000 women in Norway to determine if pregnant women receiving probiotic milk throughout gestation showed a decreased prevalence of breastfeeding problems, including mastitis [ 114 ]. The findings indicated that the consumption of probiotic milk (La-5, Bb12, and LGG) was directly associated with the prevalence of mastitis [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regrettably, the experimental data have not been fully published to date. Karlsson et al [30] published a cohort study of more than 50,000 women in Norway to examine whether pregnant women taking probiotic milk during pregnancy had a decreased incidence of breastfeeding complications, including mastitis. The results showed that the intake of probiotic milk is positively correlated with the risk of mastitis incidence.…”
Section: Plos Onementioning
confidence: 99%